Policies and mechanisms for enhancing the resource management in cloud computing: a performance perspective. (8th May 2020) - Bansal, Mitali; Malik, Sanjay Kumar; Dhurandher, Sanjay Kumar; Woungang, Isaac
Resource management is among the critical challenges in cloud computing since it can affect its performance, cost, and functionality. In this paper, a survey on policies and mechanisms for enhancing the resource management in cloud computing is proposed. From a performance perspective, several resource management schemes for cloud computing are investigated and qualitatively compared in terms of various different parameters such as performance, response time, scalability, pricing factor, throughput, and accuracy, providing some fundamental knowledge based for researchers in the cloud computing area. We also classified various cloud computing techniques based on various policies like capacity allocation, admission control, load balancing and energy optimisation. Further, we divided defined techniques on the basis of various parameters like low, medium, high time span time techniques, reliability, performance, availability to name a few.